TINJAUAN YURIDIS PUTUSAN MAHKAMAH AGUNG NOMOR 574K/Pid.Sus/2018 TENTANG MENTRANSMISIKAN DOKUMEN ELEKTRONIK DENGAN MUATAN ASUSILA - Karnofi Andrian; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The Information and Electronic Law regulates various types of criminal acts carried out in a modern way, namely the use of electronic media as a means to commit criminal acts, one of which is the distribution of content that is immoral or pornographic. In the case of Baiq Nuril with the principal of SMAN 7 Mataram, in this case the victim was reported for allegedly distributing immoral or pornographic content. From the research problem there are two problem formulations, first, how is the principle of justice in the decision No. 574k / pid.sus / 2018 about transmitting electronic documents with immoral content? second, How is the Legal Analysis Article 27 paragraph (1) of Law No. 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information on Electronic Transactions?This type of research is classified in normative legal research conducted by examining mere literature or secondary data. The data used are primary, secondary and tertiary legal materials.From the research, there are two things that can be concluded. First, the Judge's decision to the victim should reflect the value of justice. The judge did not pay attention to the reason why the defendant recorded evidence of the conversation. Second, the violation in Article 27 paragraph (1) of the Act on Transaction and Electronic Information cannot be separated and must refer to the provisions of Article of decency in the Criminal Code, in connection with that, the element in public must be a very important element, because the Electronic Transaction Information Act in no way provides sufficient understanding and understanding in relation to Article 27 paragraph (1).Keywords: Supreme Court Decision - Violation of Decency